Strategic archipelagos and tourist destinations: Canary Islands, Hawaii and Okinawa - Castelltort, Magi (Journal of the Spanish Institute for Strategic Studies, 2021)
Strategic archipelagos are usually ultraperipheral regions with high transportation and maintenance costs. However, they can also become tourist destinations for their exoticism, climate and their complementary defensive function. With the future development of West Africa, the Canary Islands will cease to be an ultraperipheral territory to regain its historic strategic role, which will require a coexistence between the tourist and the military clusters. The analysis of similar cases, such as Hawaii (United States) and Okinawa (Japan), could help develop an optimal integration of both clusters for the benefit of the local economy, and help consolidate a culture of defense in the archipelago.